2022
DOI: 10.3389/fphy.2022.849111
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Motion of an Oil Droplet Containing a Phospholipid and its Stability in Collectivity

Abstract: Collective cell migration (CCM) is a universal process that is responsible for various biological phenomena in living organisms. Therefore, unraveling the mechanism of CCM is critical for understanding the principles underlying such processes and for their application in biomaterials and biomedical science. Among these phenomena, unjamming/jamming transitions are particularly intriguing as they are controlled by three factors: cell motility, cell density, and cell–cell adhesion. However, there is no experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Based on related papers, [17,19–22,29] we can discuss the self‐propulsion mechanism of the BR droplet. Figures 1, 2, and 3 show the different droplet motion modes depending on the concentration of the BR component, especially [KIO 3 ] and [H 2 O 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on related papers, [17,19–22,29] we can discuss the self‐propulsion mechanism of the BR droplet. Figures 1, 2, and 3 show the different droplet motion modes depending on the concentration of the BR component, especially [KIO 3 ] and [H 2 O 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on related papers, [17,[19][20][21][22]29] we can discuss the selfpropulsion mechanism of the BR droplet. Figures 1, 2 Regarding the generation of the Marangoni flow, Thutupalli et al [17] reported that the BZ droplet was driven by convective flow, which was induced by the difference in interfacial tension on the droplet's surface.…”
Section: Discussionmentioning
confidence: 99%